2003
DOI: 10.1007/s10329-002-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Food competition in captive female sooty mangabeys ( Cercocebus torquatus atys )

Abstract: We studied the social and foraging behavior of two captive groups of sooty mangabeys under two different spatial food situations. These food conditions were clumped (food was placed in a box) and dispersed (food was dispersed over the entire enclosure). In each group five adult females and two adult males were observed. As a criterion for food competition, individual differences in the relative food intake were used. Adult female mangabeys had a linear, stable, and unidirectional dominance hierarchy. Access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(52 reference statements)
1
14
1
Order By: Relevance
“…Males consume these hard objects more often, mirroring what is known for Cebus apella (Janson, 1990;Masterson, 1996;Wright, 2005;Gunst et al, 2008) but they also incise and crush these foods more than females for a given ingestive event. What this apparently increased effort means is unclear: it may indicate that females initially process these items simply to get them into their cheek pouches, and that more complete processing is delayed until it can take place under less competitive conditions (e.g., Range and Noe, 2002;Stahl and Kaumanns, 2003). Placing the item within the cheek pouch could also be used to soften the endocarp to facilitate more effective mastication.…”
Section: Discussionmentioning
confidence: 95%
“…Males consume these hard objects more often, mirroring what is known for Cebus apella (Janson, 1990;Masterson, 1996;Wright, 2005;Gunst et al, 2008) but they also incise and crush these foods more than females for a given ingestive event. What this apparently increased effort means is unclear: it may indicate that females initially process these items simply to get them into their cheek pouches, and that more complete processing is delayed until it can take place under less competitive conditions (e.g., Range and Noe, 2002;Stahl and Kaumanns, 2003). Placing the item within the cheek pouch could also be used to soften the endocarp to facilitate more effective mastication.…”
Section: Discussionmentioning
confidence: 95%
“…If sooty mangabeys mainly experience scramble competition, no effect of rank on foraging success should have been observed [see van Schaik, 1989]. A study recently conducted on rank-related food benefits among female sooty mangabeys in captivity [Stahl, 1998] did not find an increase in agonistic interactions among females feeding on clumped compared to dispersed food conditions. However, there was a rank-related increase in foraging success when clumped food distributions were provided, as was found in our field study.…”
Section: Dominance Competition and Foraging Successmentioning
confidence: 95%
“…To date, the social system of the sooty mangabey (Cercocebus torquatus atys) has been studied only in captivity [Bernstein, 1971;Ehardt, 1988a, b;Gust & Gordon, 1991, 1994Gust, 1995;Stahl, 1998]. These authors found no particular bonds between related females [Ehardt, 1988a], and no signs of nepotism, such as support for kin or kin occupying adjacent ranks in the hierarchy [Gust & Gordon, 1994].…”
Section: Introductionmentioning
confidence: 97%
“…The impact of the distribution of food on social interactions has been particularly well studied and throws light on the functioning of social groups of primates, showing for instance that the distribution and the behaviour of males and females are strongly linked (Emlen and Oring 1977;Stahl and Kaumanns 2003;Wrangham 1979). Moreover, social influences on access to food are of critical concern in animal management (Box et al 1995;Redshaw and Mallinson 1991;Price and McGrew 1990).…”
Section: Introductionmentioning
confidence: 98%